Musil’s «On Stupidity». The Artistic and Ethical Uses of the Feminine Discursive (Studia austriaca, 2013)
Robert Musil’s 1937 address «Über die Dummheit» navigated a challenging subject in a treacherous climate for free speech and simultaneously affirmed Musil’s conception of the necessary symbiosis of aesthetics and ethics. This paper argues for a reading of the address and its preparatory notes wherein Musil’s gendered «Stupidity» (Die Dummheit) represents the ethical role of the artist, as poetic, non-conscripted voice – and, thus, of Musil himself – in a period of totalitarian brutality and linear «final solutions».